MENINGKATKAN HASIL BELAJAR MERODA SENAM LANTAI MELALUI PENGGUNAAN ALAT BANTU PEMBELAJARAN - Sabdoadi Dany Saputro; Djoko Nugroho (PJKR FKOR UNS, 2018)
This study aims to improve the learning outcomes of students of junior high school in the academic year 2017/2018 through the use of learning aids.This research is a classroom action research. This research was conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. The research subjects were students of of junior high school amount 32 students. Sources of data in this study come from teachers and students. Data collection techniques are by observation and evaluation of learning outcomes. Data analysis used descriptive techniques based on qualitative analysis with percentages.The results of the analysis of research data can be presented as follows starting from pre-action to cycle I and from cycle I to cycle II. In pre-action, students have not shown good learning outcomes, excellent categories with a percentage of 0%, good categories with a percentage of 3.125% or 1 student from 32 students, enough categories with a percentage of 53.125% or 17 students from 32 students, less categories with percentages 37.5% or 12 students from 32 students, then the category is very low with a percentage of 6.25% or 2 students from 32 students. In the first cycle the category is very good with a percentage of 0%, a good category with a percentage of 3.125% or 1 student from 32 students, enough categories with a percentage of 68.75% or 22 students from 32 students, a category with a percentage of 28.125% or 9 students from 32 students, and very few categories with a percentage of 0%, from the data there can be a number of 23 students have reached the criteria of completion while 9 students have not yet completed. In cycle II it reached a very good percentage of 0%, a good category of 18.75% or 6 students of 32 students, quite a category of 65.625% or 21 students of 32 students, a category of 15.625% or 5 students of 32 students, and less than 0% . So that from the data it can be seen that 27 students reach the criteria of completion while 5 students have not finished with the number of students 32 students.The conclusion of this study is that the use of learning aids can improve the learning outcomes of floor gymnastics of junior high school.